PENGARUH INTERAKSI PARASOSIAL PADA KONTEN SARA WIJAYANTO “DIARY MISTERI SARA” TERHADAP KESEHATAN MENTAL SARADDICTS SURABAYA - Ninis Abiyu Ghinanda, Labibah; Zusyana D, Ratnaningrum; Lailiyah, Fatihatul (MAJAPAHIT POLICY, 2021)
In social life, if humans never communicate with other people, they will be isolated from the environmentPublic. The influence of this isolation will certainly bring up mental stress which in the end brings people out of balance(mental disorders). Sara Wijayanto's mystical genre content with the title "Sara's Mystery Diary" explains several stories that sometimes havesimilarities with the stories and experiences (depressed, depressed, hopeless) experienced by Saradicts so that they feel close to the charactersthe media even though they have never met at all. This is then referred to as parasocial interaction. The purpose of this research is todetermine the magnitude of the influence of Parasocial Interaction on Sara's Mystery Diary content on the Mental Health of Saraddicts Surabaya. Parasocial interactionseen based on indicators of similarity of experience (empathy) and admiration (work, life, how to explain) Sara Wijayanto. MethodThis study uses quantitative methods. To test the hypothesis, the data analysis technique used is path analysis with the equationfirst (simple linear regression) and the second equation (multiple linear regression). The results of this study indicate that this research provesthe influence of Parasocial Interaction on mental health Saraddicts Surabaya. However, the effect is small and is more towards communicationempathy. Meanwhile, the influence of parasocial interaction through the variables of viewing frequency and age has no effect on mental health. InteractionThe parasocial events that occur in Sara's Mystery Diary have more influence on empathic communication, which means effective communicationshows a sense of mutual understanding between the communicator (Sara Wijayanto) and the communicant (Saraddicts Surabaya)